Does End-Expiratory Occlusion Test Predict Fluid Responsiveness in Mechanically Ventilated Patients? A Systematic Review and Meta-Analysis. Issue 6 (December 2020) - Si, Xiang; Song, Xiaodong; Lin, Qiwen; Nie, Yao; Zhang, Guanrong; Xu, Hailin; Chen, Minying; Wu, Jianfeng; Guan, Xiangdong
ABSTRACT: Background: We performed a systematic review and meta-analysis of studies investigating the end-expiratory occlusion (EEO) test induced changes in cardiac index (CI) and in arterial pressure as predictors of fluid responsiveness in adults receiving mechanical ventilation. Methods: MEDLINE, EMBASE, Cochrane Database, and Chinese database were screened for relevant original and review articles. The meta-analysis determined the pooled sensitivity, specificity, diagnostic odds ratio, area under the receiver operating characteristic curve (AUROC), and threshold for the EEO test assessed with CI and arterial pressure. In addition, heterogeneity and subgroup analyses were performed. Results: We included 13 studies involving 479 adult patients and 523 volume expansion. Statistically significant heterogeneity was identified, and meta-regression indicated that prone position was the major sources of heterogeneity. After removal of the study performed in prone position, heterogeneity became nonsignificant. EEO-induced changes in CI (or surrogate) are accurate for predicting fluid responsiveness in semirecumbent or supine patients, with excellent pooled sensitivity of 92% (95% CI, 0.88–0.95, I 2  = 0.00%), specificity of 89% (95% CI, 0.83–0.93, I 2  = 34.34%), and a summary AUROC of 0.95 (95% CI, 0.93–0.97). The mean threshold was an EEO-induced increase in CI (or surrogate) of more than 4.9 ± 1.5%. EEO test exhibited better diagnostic performance in semirecumbent or supine patients than prone patients, with higher AUROC (0.95 vs. 0.65; P  < 0.001). In addition, EEO test exhibited higher specificity (0.93 vs. 0.83, P  < 0.001) in patients ventilated with low tidal volume compared with normal or nearly normal tidal volume. However, EEO test was less accurate when its hemodynamic effects were detected on arterial pressure. EEO-induced changes in arterial pressure exhibited a lower sensitivity (0.88 vs. 0.92; P  = 0.402), specificity (0.77 vs. 0.90; P  = 0.019), and AUROC (0.87 vs. 0.96; P  < 0.001) compared with EEO-induced changes in CI (or surrogate). Conclusions: EEO test is accurate to predict fluid responsiveness in semirecumbent or supine patients but not in prone patients. EEO test exhibited higher specificity in patients ventilated with low tidal volume, and its accuracy is better when its hemodynamic effects are assessed by direct measurement of CI than by the arterial pressure. Abstract : Supplemental Digital Content is available in the text